The Great Code(r) Of Serbian Literature - Damjanov, Sava (Slavica Lodziensia, 2017)
Koder’s life and work still remain a big secret and mysterious code of Serbian literature: this writer is defi ned as a precursor of (post) modernism 20th and 21th century. During his lifetime (1806–1891) as a writer he was not accepted: after death is all but forgotten. Innovations introduced in the literature of his contemporaries were distant and vague, but they fi t perfectly into the context that has become the dominant one hundred years later. Koder’s life destiny and fate of his work here is viewed as a whole, and in the second part analyzes his relationship with symbolism and early modern in the late 19th century. In this way, Djordje Marković Koder appears as the forerunner of modern literary and artistic process.